CONNECTING SOUTH EAST ASIA: A BLUEPRINT FOR ASEAN CONNECTIVITY - Susantono, Bambang (Jurnal Transportasi, 2011)
The Association of Southeast Asian Nations (ASEAN) was established on August 8, 1967, when foreign ministers of five countries, consisting of Indonesia, Malaysia, the Philippines, Singapore, and Thailand, met in Bangkok and signed the ASEAN Declaration. The regional grouping has made the most progress in economic integration, aiming to create an ASEAN Community by 2015. Recently, the Member Countries of the ASEAN have accepted the concept of ASEAN Connectivity, which emphasized on the three pillars regional cooperation of security, socio-cultural, and economic integration. In particular, ASEAN Connectivity is expected: (1) to enhance trade, investment, tourism, and development, (2) to narrow development gaps, and (3) to facilitate people-to-people contacts. As a preparation to adapt with a new system, Indonesia is geared to improve its domestic connectivity as a prerequisite of regional connectivity. In Indonesiaâs view, regional connectivity should help empower and develop the local economies, as an effort to narrow the development gaps within ASEAN. To fulfill these goals, Indonesia needs to strengthen its physical connectivity through better transportation infrastructure. However, to support trade facilitation, good transportation infrastructure alone is not sufficient. It needs to be enhanced with ICT infrastructure, which is crucial in supporting trade facilitation through its ability to facilitate information exchange and to reduce the cost of doing business. This paper aims to explore how Indonesiaâs domestic connectivity coops with the concept of ASEAN connectivity. Some data and various existing policies in their effort to accomplish ASEAN connectivity will be explored. With the new legal framework in ICT and transportation, the performance of the ICT and transportation system in Indonesia is expected to ameliorate, hence supporting the development of other sectors, and this will ultimately lead to the realization of ASEAN Connectivity.Keywords: ASEAN connectivity, domestic connectivity, economic integration, transportation policy, ICT infrastructure.